Philippine Competition Policy in Perspective - Erlinda M. Medalla (Philippine Institute for Development Studies (PIDS), 2002)
Although justification for competition policies is well founded in the economic literature, there is a need to understand their implications more fully, brought about not just by what is happening in the global arena but even more importantly by various comprehensive policy reforms that have been implemented in recent years. And while there may be a general consensus that competition is good, there is vagueness in the minds of many and uncertainty about the need for competition policy and how competition should be enforced. This paper aims to contribute to the growing discussion on how to proceed from here. Towards this end, the paper first outlines the framework for competition policy in the Philippine setting. It then attempts to assess the state of competition in the Philippines. What has the Philippines done along the framework of competition policy and what has been the impact on the state of competition in the different sectors of the Philippine economy? A general assessment is made across the different sectors of the economy by looking at what major factors are present that could determine the state of competition in the different sectors. It also looks at policy reforms that have been implemented to improve the state of competition in these sectors. Finally, in conclusion, the paper addresses the issues that confront competition policy and suggests possible approaches towards formulating and implementing a workable competition policy for the Philippines.
Keywords: 330; competition; competition policy; market power; government policies and regulation; reforms; Wettbewerb; Wettbewerbspolitik; Marktmacht; Handelsliberalisierung; Institutioneller Wandel; Philippinen